Exit, Voice, and Loyalty in the Italian Public Health Service: Macroeconomic and Corporate Implications - Adelaide Ippolito; Cira Impagliazzo; Paola Zoccoli (The Scientific World Journal)
The paper analyses how customers of public health organizations can express their dissatisfaction for the services offered to them. The main aim is to evaluate the effects that possible dissatisfaction of Italian public health service customers can have on public health organizations. We adopted the methodological scheme developed by Hirschman with exit, voice, and loyalty, considering the macroeconomic and corporate implications that it causes for Italian public health organizations. The study investigated the effects developed by exit of the patients on the system of financing of local health authorities considering both the corporate level of analysis and the macroeconomic level. As a result, local health authority management is encouraged to pay greater attention to the exit phenomena through the adoption of tools that promote loyalty, such as the promotion of voice, even if exit is not promoting, at a macroeconomic level, considerable attention to this phenomenon.